Quantification of endogenous phytochemicals and determination of their exogenous effects in somatic embryogenesis pathways of white and water yams - Ossai, C.; Balogun, M.; Maroya, N.; Sonibare, M.A. (Springer, 2023)
In vitro propagation of yam via organogenesis is constrained with low multiplication rate. Somatic embryogenesis (SE) has shown rapid multiplication potentials in yam. However, it has not been adopted by practical seed system scenarios due to genotype specificity. Reports have shown that SE is regulated endogenously by phytochemicals, but this is yet to be elucidated for yam. This study identified, quantified endogenous, and evaluated effects of exogenous application of selected identified phytochemicals in yam SE. Callus was induced from in vitro axillary bud explants of three Dioscorea rotundata genotypes in Murashige and Skoog (MS) medium containing 9.1 µM 2,4-dichlorophenoxyacetic acid and 5.4 µM naphthaleneacetic acid. Plantlets were regenerated using MS medium containing 4.4 µM benzylaminopurine and 34.0 µM uniconazole-P. Endogenous phytochemicals associated with axillary bud, calluses, and plantlets were identified and quantified using GC/MS. Effect of selected identified phytochemicals on the genotypes was investigated in a 5 × 6 factorial in completely randomized design (r = 3). Data taken on plantlet regeneration was analyzed using ANOVA at α0.05. A total of 27, 22, and 35 phytochemicals were identified in Kpamyo, Ekiti2a, and Asiedu, respectively. Hexamethylcyclotrisiloxane (36.4%, Kpamyo), Tris-tert-butyldimethylsilyloxy-arsane (59.3%, Ekiti2a), and 4-methyl-2-trimethylsililoxy-acetophenone (52.7%, Asiedu) were highest in callus. N-Methyl-1-adamantaneacetamide (31.8%, Kpamyo) and Tris-tert-butyldimethylsilyloxy-arsane (52.7%, Ekiti2a, Asiedu) were highest in plantlets while Tris-tert-butyldimethylsilyloxy-arsane (41.2%, Kpamyo), hexamethylcyclotrisiloxane (55.8%, Ekiti2a), and erythro-9,10-dibromopentacosane (38.9%, Asiedu) were highest in axillary bud. Plantlet regeneration differed significantly among phytochemicals and ranged from 0.7 ± 0.3 (control) to 4.5 ± 0.5 (40.5 µM phenylacetic acid). Also, genotype × phytochemical interactions on number of plantlets regenerated were significant, and mean values ranged from 0.0 ± 0.0 (TDa2014, 4.8 µM decamethyltetrasiloxane) to 7.0 ± 1.7 (TDa2014, 40.5 µM phenylacetic acid). The application of 40.5 µM phenylacetic acid enhanced plantlet regeneration in Kpamyo and TDa2014 by 5.39% and 343.04%, respectively.